2006
DOI: 10.1039/b608066a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular chirality of columnar mesophases consisting of H-bonded complexes of melamine and polycatenar benzoic acids

Abstract: The present work describes a series of H-bonded complexes consisting of a melamine derivative and polycatenar acids that show columnar liquid crystalline behaviour. Chirality has been transferred from the molecular blocks (either the acids, A3* and A4*, or the melamine, T2*) to the columnar organization. Particular effort and attention has been paid to structural characterization by NMR techniques [1D NMR spectroscopy and diffusion-ordered spectroscopy (DOSY) experiments] of the complexes in solution. The meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The CvO stretching band of pure DBA sample appeared at 1686 cm 21 , corresponding to the cyclic dimeric form. However, for the DM11 and DM31 samples, broad shoulders around 1696-1714 cm 21 for the antisymmetrical stretching band of the carboxy group could be observed, which suggested that the carboxyl head groups in DBA units formed hydrogen-bonding interaction with amino groups of melamine (32). Besides, hydrogenbonding interaction between carboxyl and amino groups was also responsible for the disappearance of the strong CvO stretching band at 1686 cm 21 .…”
Section: Preparation and Characterisations Of The Supramolecular Assementioning
confidence: 81%
“…The CvO stretching band of pure DBA sample appeared at 1686 cm 21 , corresponding to the cyclic dimeric form. However, for the DM11 and DM31 samples, broad shoulders around 1696-1714 cm 21 for the antisymmetrical stretching band of the carboxy group could be observed, which suggested that the carboxyl head groups in DBA units formed hydrogen-bonding interaction with amino groups of melamine (32). Besides, hydrogenbonding interaction between carboxyl and amino groups was also responsible for the disappearance of the strong CvO stretching band at 1686 cm 21 .…”
Section: Preparation and Characterisations Of The Supramolecular Assementioning
confidence: 81%
“…10,12‐Pentacosadiynoic acid (PCDA) was purchased from Tokyo Chemical Industry (Japan), and purified by recrystallization from petroleum ether before use. 2,4‐diamino‐6‐octadecyl amino‐1,3,5‐triazine (T) was synthesized in analogy to the previous procedure . All other reagents and solvents were of analytical grade and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…2,4-diamino-6-octadecyl amino-1,3,5-triazine (T) was synthesized in analogy to the previous procedure. 30 All other reagents and solvents were of analytical grade and used as received. Milli-Q water (Millipore, Bedford, MA; 18.2 MΩ · cm) was used in all cases.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…The mesomorphic properties can be easily modified by miscellaneous proton donors and acceptors, and new LC properties, which are different from those of their original moieties, can be easily obtained by the introduction of supramolecular structures. Many kinds of H‐bonds and building elements have been explored in the H‐bonded structures to stabilize LC phases 10–17. Therefore, side‐chain LC polymers consisting of polymer backbones, flexible spacers, and mesogenic pendants have great potentials in various utilizations as novel technological materials, such as optical switching elements, optical storage devices, and information displays.…”
Section: Introductionmentioning
confidence: 99%